ChemInform Abstract: Synthesis and Structural/Physical Properties of U3Fe2Ge7: A Single‐Crystal Study. Issue 49 (December 2015) - Henriques, Margarida S.; Gorbunov, Denis I.; Waerenborgh, Joao C.; Pasturel, Mathieu; Andreev, Alexander V.; Dusek, Michal; Skourski, Yurii; Havela, Ladislav; Goncalves, Antonio P.
Abstract: Single crystals of U3 Fe2 Ge7 are grown from an equimolar mixture of the elements in a tin flux (graphite crucible in evacuated silica tubes, 1273 K, 2 d; cooling to 573 K with a rate of 5 K/h).